Role of Lok Adalats in Settlement of Motor Accident Claims in India (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The increasing number of road accidents in India has resulted in a substantial rise in motor accident compensation claims before Motor Accident Claims Tribunals (MACTs). Delayed adjudication, procedural complexities, pendency of cases, and the economic hardships faced by victims and their families have necessitated the adoption of alternative dispute resolution mechanisms. In this context, Lok Adalats have emerged as an effective and people-oriented institution for expeditious settlement of motor accident claims in India. Established under the Legal Services Authorities Act, 1987, Lok Adalats provide inexpensive, speedy, and amicable settlement of disputes through conciliation and compromise. Their functioning aligns with the constitutional mandate of ensuring equal access to justice under Articles 14 and 39A of the Constitution of India.Motor accident claim disputes constitute one of the largest categories of cases settled through National Lok Adalats across the country. These forums significantly reduce litigation costs, avoid prolonged court proceedings, and facilitate timely compensation to victims. The collaborative participation of insurance companies, claimants, legal aid authorities, and judicial officers has enhanced the efficiency of Lok Adalats in resolving compensation disputes. The paper critically examines the legal framework governing Lok Adalats and motor accident compensation claims, analyses judicial interpretations, evaluates the role of Legal Services Authorities, and highlights the practical challenges faced in settlement proceedings. The article further examines the impact of Lok Adalats in reducing pendency of MACT cases and promoting social justice.The study concludes that Lok Adalats have become an indispensable mechanism in the Indian justice delivery system for settlement of motor accident claims. However, concerns regarding inadequate compensation, unequal bargaining power, lack of legal awareness, and pressure for compromise require systematic reforms. Strengthening institutional capacity, adopting digital mechanisms, enhancing awareness among accident victims, and ensuring fairness in compensation settlements are necessary for improving the effectiveness of Lok Adalats in motor accident claim adjudication.